1970
DOI: 10.1177/002224377000700313
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk in Mail-Order and Retail Store Buying

Abstract: This study investigates differences in risk perception between buying by mail and buying from a store and/or salesman. For 20 products studied, consumers perceived more risk in the mail-order situation than in the store/salesman situation. The relationship between perceived risk and selected socioeconomic variables is examined. Implications for further research are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
3

Year Published

1987
1987
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(71 citation statements)
references
References 1 publication
3
64
1
3
Order By: Relevance
“…Previous research on perceived risk has consistently found that patronage mode is associated with perceived risk. Previous researchers have found consumers to associate more risk with home shopping (e.g., telephone, catalog, and door-to-door sales) than with store shopping (i.e., department stores) (e.g., Cox & Rich, 1964;Festervand, Snyder, & Tsalikis, 1986;Korgaonkar, 1982;Kwon et al, 1991;Schiffman, Schus, & Winer, 1976;Simpson & Lakner, 1993;Spence, Engel, & Blackwell, 1970). For example, Cox and Rich (1964) found greater perceived overall risk for telephone shopping as compared with store shopping.…”
Section: Perceived Risks In Home Shoppingmentioning
confidence: 95%
“…Previous research on perceived risk has consistently found that patronage mode is associated with perceived risk. Previous researchers have found consumers to associate more risk with home shopping (e.g., telephone, catalog, and door-to-door sales) than with store shopping (i.e., department stores) (e.g., Cox & Rich, 1964;Festervand, Snyder, & Tsalikis, 1986;Korgaonkar, 1982;Kwon et al, 1991;Schiffman, Schus, & Winer, 1976;Simpson & Lakner, 1993;Spence, Engel, & Blackwell, 1970). For example, Cox and Rich (1964) found greater perceived overall risk for telephone shopping as compared with store shopping.…”
Section: Perceived Risks In Home Shoppingmentioning
confidence: 95%
“…A number of studies have examined the relative riskiness of products drawn from different product classes [12] [14] [16] [29] [31]. A limited amount of published research has focused on risk within a given product class, generally in the context of brand choice [lo] [19] [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior retailing research suggests that the perceived risk of a product is transferable to the store that sells the product (6,8,21,43,55). Therefore, generalizing across types of retail outlets (different sources such.…”
Section: Intermodal Differencesmentioning
confidence: 99%
“…Perceived risk and/or its reciprocal, self-confidence, has been a variable of interest to many researchers in comparing buying by mail with buying from a store (10,55), and in comparing in-home shoppers with non-in-home shoppers (6,10,31,39,46,53,58). Some consumers may consider in-home shopping too risky because of the lack of opportunity to examine products prior to a purchase, and because of the difficulties in returning unsatisfactory merchandise.…”
Section: Perceived Riskmentioning
confidence: 99%
See 1 more Smart Citation